24.8k views
11 votes
Create an equivalent system of equations using the sum of the system and the first equation.

-5x + 4y = 8
4x + y = 2
•.
-5x + 4y = 8
x + 5y = 10
O
-5x + 4y = 8
-x + 5y = 10
-5x + 4y = 8
9x + 5y = 2
• d
-5x + 4y - 8
A
-x + y = 10

User Kiskae
by
5.1k points

1 Answer

9 votes

Answer:

B-

-5x + 4y = 8

-x + 5y = 10

Explanation:

x+ 4y = 8, we'll call this A

4x + y = 2, we'll call this B

To create the equivalent system, you can mulitply or divide by a coeffecient, to get a pure solution. If you add or subtract, the system is unchanged.

We are adding A to B

x + 4y = 8 + 4x + y = 2

5x + 5y = 10, we'll call this C.

The new equation is the basis for the equivalent system, where C replaces B

User Scott Klarenbach
by
4.7k points